Implementasi Nilai Agama Moral Anak Usia Dini Melalui Pembelajaran Market Day - Eko Setiawan (ABNA : Journal of Islamic Early Childhood Education, 2021)
The standard level of achievement of children's development in aspects of religious moral values that are lacking. The purpose of the study was to determine the implementation of moral religious values for early childhood through market day learning. This type of research is descriptive qualitative, carried out at PAUD Aqila Yasmin Ceper, Klaten in April – August 2020. The research subjects were group A teachers and PAUD head informants. Collecting data using observation, interviews, and documentation. The validity of the data was carried out by means of triangulation of sources and methods, then analyzed with the Interactive Model. Process of implementing moral religious values consists of three stages, preparation, implementation and evaluation. The development of moral religious values through the method of habituation in market day activities using the principle of Playing While Learning, Stimulation of Integrated Experimental Learning.